Power Relations of The National Sharia Council and the Construction of Islamic Identity through Sharia Discourse Masification - Rahim, Abdul; Halimatuzzahro (JURNAL PENELITIAN, 2021)
This paper attempts to describe the Islamic discourse echoed by the National Sharia Council (DSN) as an ideal solution in products/programs that are suitable in Islamic law, but in practice it becomes a sheath of domination that is accepted by the Muslim community as taken for granted. The practice of sharia discourse that create new capitalism occur in Banks Syariah, BPJS Syariah, and Cooperatives Syariah. The power relations of the National Sharia Council which claime sharia discourse as an ideal concept, behind which there are capitalist interests that are networked with non-sharia (conventional) products / programs. Through the power of the DSN as a knowledgeable authority, the Muslim community as a target began to hegemony over the sharia discourse, because the cult of the DSN represented the intellectual authority in Islamic law. Meanwhile, consumptive practices in the sharia discourse can be seen in the concept of sharia tourism, sharia hotels, and syar'i hijab. The syar'i hijab, which is the mainstay of capitalism in fashion products targeting the Muslim community, forms excessive consumerism in decoration (tabarruj) rather than the simplicity idealized in Islamic law (zuhud / asceticism). Ideal sharia practices and in accordance with Islamic law in economic terms can be echoed again through the maximalize management of Baitul Mal as an accommodating forum for Zakat Mal, Infaq, waqf and others.